Transparency in Central Bank Financial Statement Disclosures - Sullivan, Kenneth (IMF Working Papers; Working Paper ;, 2005)
The IMF's development of the Code of Good Practices on Transparency in Monetary and Financial Policies and the introduction of safeguards assessments have increased emphasis on transparency of the disclosures made in central bank financial statements. This paper, which updates WP/00/186, looks at the disclosure requirements for central banks under International Financial Reporting Standards and provides practical guidance for those responsible for preparing central bank financial statements.